MIXOLOGIST PEREMPUAN DI KOTA MAKASSAR - MUH. ZAINUDDIN BADOLLAHI; M. AHYAR ALMY (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2019)
In uncovering female mixologists as actors from the tourism industry, on the basis of the theory of cultural concepts, work ethic, and community views. The work ethic of women to actualize themselves in order to improve the family economy is based on socio-cultural, educational, technological and environmental factors. although the role of women is able to contribute significantly to their own, family and community departments but social views about their profession as mixologists which add a series of stereotypes to women that have a negative impact on female workers including mixologist workers.